APPLICATION OF THE PROJECT BASED LEARNING MODEL IN IMPROVING STUDENT DISCIPLINE IN PAI SUBJECTS AT SMP ISLAM INSAN KAMIL AN-NAHDLIYAH - Ramadhani Zalsanudin, Virgie; Masnawati, Eli (LP2M Institut Agama Islam Al-Khiarat Pamekasan, 2024)
This study aims to determine the effectiveness of the use of the project-based learning model applied to PAI subjects in improving the disciplinary attitude of students of Insan Kamil An-Nahdliyah Islamic Junior High School, Wonoayu District. In this study, a qualitative type of research is used, the reason the author uses this method is because this research is a study with ideas that are built more conceptually. Data collection techniques using various literary sources such as books, journals and previous research that has been carried out. From the various reference materials of the Library, they are then analyzed critically and in-depth in order to support their propositions and ideas. Based on the results and discussion, the application of the project-based learning model is able to improve student discipline in Islamic religious education (PAI) subjects. The application of the Project Based Learning (PjBL) learning model has proven to be effective in improving discipline and developing students' character in PAI subjects at SMP Islam Insan Kamil An-Nahdliyah. This learning model is recommended to be applied in other schools as an effort to improve the quality of Islamic religious education.